Implementation of singing groups for postnatal depression: experiences of participants and professional stakeholders in the SHAPER-PND randomised controlled trial - Han, Emeline; Davis, Rachel; Soukup, Tayana; Bradbury, Alexandra; Williams, Julie; Baldellou Lopez, Maria; Greenwood, Lorna; Bind, Rebecca; Estevao, Carolina; Osborn, Tim; Dye, Hannah; Priestley, Kristi; et al. (Frontiers in Health Services, 2025)
BackgroundThere is a rapidly growing evidence base for the effectiveness of creative health interventions in improving mental health, but few studies have explored implementation and scaling of these interventions. The aim of this study was to evaluate the perceived acceptability, appropriateness, and feasibility of a ten-week singing group programme (Breathe Melodies for Mums (M4M)) for mothers experiencing symptoms of postnatal depression (PND) and their babies as well as the programme ingredients that affected these implementation outcomes.MethodsA mixed methods design was adopted. Quantitative data was collected via the Acceptability of Intervention Measure (AIM), Intervention Appropriateness Measure (IAM), and Feasibility of Intervention Measure (FIM) from 109 intervention participants at 6, 20, and 36 weeks and analysed descriptively. Qualitative semi-structured interviews were conducted with 22 programme participants and 15 professional stakeholders involved in implementing the programme. Qualitative data were analysed using framework analysis.ResultsQuantitative results showed high levels of acceptability, appropriateness, and feasibility among M4M participants, with median scores of 5/5 achieved on the AIM, IAM and FIM at 20 and 36-week follow up. Qualitative results gave insights into the ingredients of M4M that made the programme acceptable, appropriate, and feasible to participants and professional stakeholders. These included “project” ingredients (dose, design, content), “people” ingredients (social composition, activity facilitation), and to a lesser extent, “context” ingredients (setting, project set-up). While participant and stakeholder experiences were largely positive, some challenges and suggestions for improvement were also identified, including broadening recruitment strategies to reach more women.ConclusionM4M was highly acceptable, appropriate, and feasible to participants and stakeholders. By identifying the “core” ingredients that facilitated implementation success and strategies to address implementation barriers, these findings have important implications for future implementation and scale-up of M4M and similar creative health programmes. Clinical Trial Registrationidentifier (NCT04834622).